OGC P26 The role of inadequate analgesia in care escalation after oesophagectomy. (7th December 2022) - Bramer, Solange; Antonowicz, Stefan; Ash, Stephen; Maynard, Nick
Abstract: Background: There is a paucity of data describing the incidence and causes of escalation in level of care after oesophagectomy for cancer. This study aimed to address this, including the description of baseline predisposing variables, and contrasting the profile of care escalation among different surgical approaches to oesophagectomy. Methods: This was a retrospective analysis of a prospectively maintained database ('CODA') at a UK tertiary centre. CODA is a bespoke, high-quality resource, based on senior clinician and data scientist data entry at every stage of the care of the patient's pathway. Complications are updated weekly using the Esophageal Complications Consensus group definition-set. The inclusion criteria were anyone undergoing cancer oesophagectomy between 01/06/2015 and 31/05/2021. Exclusion criteria included patients not on the 'Enhanced Recovery after Surgery' pathway and patients with delayed extubation (>2 days post-operatively). Escalation of care was defined as re-admission to the intensive care unit (ICU) or re-intubation on ICU. Standard care at our centre is to maintain epidural analgesia for four days after surgery. Inadequate analgesia was defined as more than one reference to inadequate pain control in the first four days after surgery when the patient deteriorated and required care escalation. Characteristics were compared between patients with and without care escalation, and between patients with and without respiratory failure related to inadequate analgesia. Results: From 448 oesophagectomys, 42 patients had escalation in their level of care (9.38%). Baseline characteristics between oesophagectomy patients with and without escalation in care were similar, except for escalated patients more likely to have squamous cell carcinoma histology (28.6% vs 14.3%, P = 0.02). 20.0% of 3-phase oesophagectomy patients required care escalation but this just failed to achieve significance when compared with other oesophagectomy approaches (9.6%, P = 0.06). Of escalated patients, 35.7% had respiratory failure related to inadequate analgesia, 33.3% had respiratory failure not related to inadequate analgesia and 31.0% did not have respiratory failure as the reason for care escalation. The major cause of respiratory failure not related to analgesia was pneumonia (6 of 14, 42.9%) and the most frequent cause of non-respiratory failure associated escalation in care was re-operation (5 of 13, 38.5%). Inadequate analgesia was more commonly a contributing factor to escalation in care after left thoracoabdominal oesophagectomy compared to all other approaches (11 of 18 [61.1%] vs 4 of 24 [16.7%], P = 0.003). Conclusions: The overall rate for escalation in care in this centre was low at 9.38%. This figure may be useful for benchmarking and ongoing research into morbidity after oesophagectomy. There was no clear influence from baseline characteristics or surgical approach on the rate of escalation in care. Respiratory failure contributed to escalation in care for the majority of patients. Our data indicates that left thoraco-abdominal incisions are particularly sensitive to inadequate analgesia, which suggests that effective analgesic rescue plans are especially critical after this type of oesophagectomy.